Using drama activities to teach beginner’s French to Chinese students at a tertiary institution in Hong Kong: An exploratory case study - Abenoja, Zarina Marie Krystle M.; DeCoursey, Matthew (Studies in Second Language Learning and Teaching, 2019)
The exam-oriented education system in Hong Kong has created a language learning environment that is largely confined to traditional classroom settings, which may not take best advantage of students’ abilities to relate what they have learnt in class to real-life scenarios. Such learning environments may have implications for the way second language learners learn a new language. Numerous studies suggest that drama activities used in language classrooms can enhance second language learning. These studies put forward tasks that generate pleasant and rewarding experiences, enhance confidence and subsequently increase motivation to learn a language. By focusing on students studying in a beginning French course at a tertiary institution in Hong Kong, this article reports on how drama activities make a target language more enjoyable and easier to recall. Classroom observations and interviews with students (N = 30) revealed that learning French via drama had a number of positive effects on second language learners especially in terms of their confidence. The learning of French through drama may provide a language learning environment that enables students to apply their French language skills more effectively in real-life situations.